2003
DOI: 10.1590/s1678-77572003000400011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the deflasking delay time on the displacements of maxillary denture teeth

Abstract: he purpose of this study was to investigate the displacement of teeth occurring in dentures following storage in water at a temperature of 37ºC. Ten maxillary dentures were constructed with Classico heat-cured acrylic resin using conventional metal flasks. Metallic reference pins were placed on the incisal border of the central incisors (I), buccal cusp of the first premolars (PM), and mesiobuccal cusp of the second molars (M). The acrylic resin was polymerized twelve hours after final flask closure in a water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
(21 reference statements)
1
5
0
1
Order By: Relevance
“…Considering that the change promoted by both techniques was not statistically different, the additional flask cooling by bench storage for 3 hours was not sufficient to modify the dimensional conditions established by the cooling in the polymerizing water in relation to the released stress. Similar results were also observed in the displacement of teeth in the transverse and anteroposterior distances, when the dentures were invested in a metallic flask with the traditional acrylic resin pressure method, associating the water-cooling and bench storage methods 7 . The dimensional stability of the teeth distances was probably due to the similar amount of water absorbed by mass volume, an occurrence also dependent upon the residual monomer amount present during the initial storage period.…”
Section: Discussionsupporting
confidence: 74%
“…Considering that the change promoted by both techniques was not statistically different, the additional flask cooling by bench storage for 3 hours was not sufficient to modify the dimensional conditions established by the cooling in the polymerizing water in relation to the released stress. Similar results were also observed in the displacement of teeth in the transverse and anteroposterior distances, when the dentures were invested in a metallic flask with the traditional acrylic resin pressure method, associating the water-cooling and bench storage methods 7 . The dimensional stability of the teeth distances was probably due to the similar amount of water absorbed by mass volume, an occurrence also dependent upon the residual monomer amount present during the initial storage period.…”
Section: Discussionsupporting
confidence: 74%
“…The water storage intervals did not show statistically significant difference to each other (p>0.05) ( Table 1). This result suggests that the displacement of denture teeth due to acrylic resin base water sorption involves other factors occurring during the denture processing, such as base thickness, geometrical palate form, closure flask pressure, cooling method of the flask, different stresses released in different parts of the denture and mesiodistal tooth contact (12,14,19,20).…”
Section: Discussionmentioning
confidence: 98%
“…Results revealed that using dental stone or 50–50 mixture of plaster and stone during investing procedure resulted in smaller denture teeth displacement. Various studies have proven that tooth movement occurs during and after the processing of complete dentures (Atkinson and Grant, 1962, Consani et al, 2003, Consani et al, 2006). An understanding of this phenomenon may permit one to construct functional complete dentures that require less occlusal adjustment in the articulator and in the patient’s mouth (Mainieri et al, 1980, Molligoda Abuzar et al, 1995).…”
Section: Discussionmentioning
confidence: 99%